HUBUNGAN STRUKTUR KEPEMILIKAN PADA PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN PUBLIK INDONESIA - Diah Ningrum, Oktavia Dwi Nur; Faisal, Faisal (Diponegoro Journal of Accounting, 2014)
This background of study was operational activity of public companies in Indonesian had impact of environment. This impact made companies must did activities of corporate social responsibility, next to made a report of corporate social responsibility disclosure, or called sustainability report. Sustainability report used by shareholders to take a investment decision. Then, formulation of problem in this study was “how to ralationship of ownership structure on corporate social responsibility disclosure in Indonesian public corporation”. This study aims to know a ralationship of ownership structure on the corporate social responsibility disclosure (CSRD) in Indonesian public corporate, and provided into sustainable report of companies listed on Indonesian Stock Exchange (IDX). Ownership structure tested in this study were ownership concentration, managerial ownership, foreign ownership, and government ownership. This study using  two proxy were disclosure index, and total of sentence quantity disclosure. An dependent variable, CSRD was measured by Global Reporting Index (GRI) based on Said, et.al.research in 2009. Control variable in this study was firm value consisted of firm size, profitability, firm age, and leverage. By using a purposive sampling method, 34 listed companies of all companies listed on IDX in the study based on their 2010, 2011, and 2012 sustainable report, and data were analyzed using multiple regression. The result of empirical indicated that foreign ownership had a positive, and significant association on CSRD in disclosure index proxy. Then, a result total of sentence quantity disclosure were government ownership had a positive, and significant association on CSRD.